Implications of Metamaterial on Ultra-Wide Band Microstrip Antenna Performance - Elham A. Serria; Mousa I. Hussein (Crystals, 2020)
This study is addressing the slotted ring resonator effect on the performance of the ultra-wide band (UWB) microstrip antenna. Two types of metamaterial with double slotted ring resonators (SRR), circular (C-SRR) and square (S-SRR), are studied and implemented on back of the antenna. The design examines the effect of the number of the SRR and its position with respect to the antenna’s ground plane and the rotation of the inner and outer C-SRR rings on different antenna characteristics. The dimensions of the antenna are 45 mm × 31 mm × 1.27 mm. The implementation of the SRR increased the antenna bandwidth to cover the range from 2.2 GHz to 9.8 GHz with rejected bands and frequencies. Antenna simulated characteristics like return loss, maximum gain and radiation pattern are obtained utilizing HFSS. The return loss measurement and the VSWR of the antenna with all SRR configuration studied are in good agreement with simulated results.